Intersections between democracy, efficiency, public policies, and social justice in structural litigation: a legal study - Hogemann, Edna Raquel (Universidad Hemisferios, 2025)
The article explores the intersections between democracy, administrative efficiency, public policies, and social justice in the context of structural litigation. These judicial demands seek solutions for violations of fundamental rights that impact collectives, representing significant challenges for the judiciary and public administration. Therefore, by analyzing practical examples in Brazil, such as public civil actions aimed at restructuring health and education systems, the study discusses the role of judicial intervention in promoting social justice; it highlights how these interventions can correct structural inequalities and ensure fundamental rights while respecting the autonomy of public managers. The approach emphasizes the need to balance the effectiveness of judicial decisions with democratic sustainability, promoting inclusive public policies without compromising governance. In this context, the article underscores the importance of institutional dialogue between the powers and civil society, aiming to implement efficient solutions aligned with constitutional principles. Thus, it contributes to the strengthening of democracy and the realization of social justice in a scenario of complex collective demands.